Awareness and Usage of Reference Management Software: Perspectives of Faculty Members of University of Ilorin Nigeria - Ismail Olatunji Adeyemi; Kabir Alabi Sulaiman; Lawal Mohammed Akanbi (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
This study examined the awareness and usage of reference management software by faculty members of the University of Ilorin. Descriptive survey method was adopted for the study. The Web-based questionnaire was used to collect data for the study. The total population of the study is 1,496 people. From which the sample size of 306 was selected using Raosoft sample size calculator and total responses of 98 was returned, which represents the unit of analysis. Hence, the response rate for the study is 32%. The findings of the study revealed that EndNote and Mendeley are the most used reference management software by faculty members of the University of Ilorin (UNILORIN). Results show that faculty members were aware of EndNote and Mendeley to great extent. It was found that there is low usage of reference management software among faculty of the University of Ilorin; and that most of the faculty members have never used ProCites, Bookends, Papers and Qiqqa. It was concluded that there is a positive significant relationship between awareness and usage of reference management software by faculty members. It was recommended that faculty members should be trained on how to make use of the most used reference management software.